To find the point of intersection of these two lines, we need to set the two equations equal to each other and solve for x:
-1/2x - 6 = 7/6x + 4
To simplify this equation, let's multiply both sides by 6 to get rid of the denominators:
-3x - 36 = 7x + 24
Now, let's combine like terms:
-3x - 7x = 24 + 36
-10x = 60
Divide both sides by -10:
x = -6
Now that we have the value of x, we can substitute it back into one of the original equations to find the value of y. Let's use the first equation:
y = -1/2(-6) - 6
y = 3 - 6
y = -3
Therefore, the point of intersection is (-6, -3).
Y= -1/2x - 6 and y= 7/6x + 4
1 answer